2022
DOI: 10.3390/cancers14235811
|View full text |Cite
|
Sign up to set email alerts
|

SGLT-2 Inhibitors in Cancer Treatment—Mechanisms of Action and Emerging New Perspectives

Abstract: A new group of antidiabetic drugs, sodium-glucose cotransporter 2 inhibitors (SGLT-2 inhibitors), have recently been shown to have anticancer effects and their expression has been confirmed in many cancer cell lines. Given the metabolic reprogramming of these cells in a glucose-based model, the ability of SGLT-2 inhibitors to block the glucose uptake by cancer cells appears to be an attractive therapeutic approach. In addition to tumour cells, SGLT-2s are only found in the proximal tubules in the kidneys. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 179 publications
(293 reference statements)
1
50
0
Order By: Relevance
“…They are well tolerated and safe, and have been found to be effective in treating heart failure in patients without diabetes. The expression of SGLT2 has been confirmed in various types of cancer cells, making them a promising target for therapy [ 124 ]. recent evidence suggests that SGLT2 inhibitors may have potential as an anti-cancer therapy.…”
Section: Sglt2 Inhibitors and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…They are well tolerated and safe, and have been found to be effective in treating heart failure in patients without diabetes. The expression of SGLT2 has been confirmed in various types of cancer cells, making them a promising target for therapy [ 124 ]. recent evidence suggests that SGLT2 inhibitors may have potential as an anti-cancer therapy.…”
Section: Sglt2 Inhibitors and Cancermentioning
confidence: 99%
“…recent evidence suggests that SGLT2 inhibitors may have potential as an anti-cancer therapy. The anticancer activity of SGLT2 inhibitors has been demonstrated in such cancers as liver, pancreatic, prostate, bowel, lung, and breast cancer [ 124 ]. Some types of cancer cells express SGLT2, and SGLT2 inhibitors have been shown to induce apoptosis or inhibit the proliferation of cancer cells at high concentrations in vitro [ 125 ].…”
Section: Sglt2 Inhibitors and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, murine studies found no tumor promoter or progressor potential for dapaglafozin. 6 In addition, large meta-analyses consistently showed no increase in the overall risk of cancer or of specific cancer types. 6 Emerging evidence now suggests that SGLTs may actually play a vital role in tumor cell homeostasis, raising the attractive prospect that SGLT2is may possess anticancer properties.…”
mentioning
confidence: 99%
“…6 In addition, large meta-analyses consistently showed no increase in the overall risk of cancer or of specific cancer types. 6 Emerging evidence now suggests that SGLTs may actually play a vital role in tumor cell homeostasis, raising the attractive prospect that SGLT2is may possess anticancer properties. 6,7 The link between cancer growth and glucose dates to the pioneering studies by Otto Warburg describing increased glucose uptake and preferential use of glycolysis for energy in tumor cells versus normal cells.…”
mentioning
confidence: 99%